The coal miner's daughter - Hope, Maggie (London, England, Ebury Press, 2017)
A wealthy landlord's son, and a coal miner's daughter...Growing up in poverty, one of six siblings, Hannah Armstrong never thought she'd know anything other than her little mining town. But then she falls for Timothy Durkin, a wealthy Oxford student...Following her heart, Hannah sacrifices everything she holds dear and follows her new husband to Oxford. But will her new life of luxury be everything she expected - or will she find that once a coal miner's daughter, always a coal miner's daughter...?
Keywords: Domestic Fiction; Historical fiction; Married Couple.-- Fiction; Poverty.-- Fiction